2020
DOI: 10.1016/j.celrep.2020.108444
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Mutations in STK11 and KEAP1 Promote Ferroptosis Protection and SCD1 Dependence in Lung Cancer

Abstract: SUMMARY Concurrent loss-of-function mutations in STK11 and KEAP1 in lung adenocarcinoma (LUAD) are associated with aggressive tumor growth, resistance to available therapies, and early death. We investigated the effects of coordinate STK11 and KEAP1 loss by comparing co-mutant with single mutant and wild-type isogenic counterparts in multiple LUAD models. STK11/KEAP1 co-mutation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 42 publications
4
101
0
Order By: Relevance
“…ALOX12 has been reported to be the core enzyme in mediating lipid peroxidation and has significant correlation with glutathione peroxidase 4 (GPX4) ( 53 ). AKR1C1 protects cancer cells from ferroptosis and is considered as the ferroptosis-protective gene ( 54 ). In addition, AKR1C1 has been confirmed high basal expression levels in CRC and promotes tumor proliferation, metastasis, and drug resistance ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…ALOX12 has been reported to be the core enzyme in mediating lipid peroxidation and has significant correlation with glutathione peroxidase 4 (GPX4) ( 53 ). AKR1C1 protects cancer cells from ferroptosis and is considered as the ferroptosis-protective gene ( 54 ). In addition, AKR1C1 has been confirmed high basal expression levels in CRC and promotes tumor proliferation, metastasis, and drug resistance ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown the involvement of SCD1 in the regulation of ferroptosis [ 97 , 98 ]. Tesfay and colleagues correlated high expression levels of SCD1 found in different ovarian cancer isotypes with the synthesis of lipids implicated in protection from ferroptosis, as a mevalonate metabolite CoQ10.…”
Section: The Controversial Role Of Scd1-mediated Autophagy In Cancer and Future Research Perspectivesmentioning
confidence: 99%
“…In particular, the highest therapeutic efficacy was achieved when the SCD1 inhibitor A939572 and the ferroptosis inducer erastin were administered in combination rather than as a single agent [ 97 , 99 ]. Additionally, Wohlhieter et al identified SCD1 as an essential gene for survival and ferroptosis protection in STK11/KEAP1 co-mutant lung adenocarcinoma [ 98 ], a subset of tumors characterized by resistance to available therapies and early death [ 100 ].…”
Section: The Controversial Role Of Scd1-mediated Autophagy In Cancer and Future Research Perspectivesmentioning
confidence: 99%
“…Ferroptosis plays a key role in killing tumor cells and inhibiting tumor growth (Jiang et al, 2021;Wang H. et al, 2021). Accumulating evidence indicates that ferroptosis is involved in the biological processes of LUAD (Wohlhieter et al, 2020;Li et al, 2021;Lou et al, 2021). However, the regulation of ferroptosis remains obscure, and it is far from being applied to cancer therapy.…”
Section: Introductionmentioning
confidence: 99%